Investigation and Analysis of the Influence of Vegetative Tracheobronchial Foreign Body on Airflow Field - Yudong Bao; Shengqian Qu; Kai Li (Applied Bionics and Biomechanics)
The BSL k-ω turbulence model was used to numerically simulate the inspiratory airflow of the airway with foreign bodies using a real CT scan human airway model. The paper selects three foreign bodies with different diameters, three different foreign body positions, and three different breathing intensities, and the FLUENT software is used to perform numerical simulation. This study has found that the increase in the diameter of the foreign body and flow velocity will make the flow structure in the airway more complicated. The airway pressure will increase so that the resistance of breathing will increase, and the shear force will also increase, which hurt the airway. The impact of the foreign body on the left side on the flow structure in the airway is less than that of the foreign body on the right side. The foreign body on the left side causes the pressure drop in the airway to be higher than that on the right side. Moreover, sharp changes in pressure driving force and airway curvature will affect the airflow pattern of the central airway. We concluded that foreign matter has a great influence on the characteristics of the airflow structure, and more research is needed to increase the understanding of the airflow pattern under the condition of foreign matter in the airway, and the research helps doctors avoid the influence of airflow when removing foreign bodies in the airway.